Prostaglandin E2 and Connexin 43 crosstalk in the osteogenesis induced by extracorporeal shockwave. (September 2016) - Chen, Youbin; Xu, Jiankun; Liao, Haojie; Ma, Zebin; Zhang, Yuantao; Chen, Hongjiang; Huang, Zhonglian; Hu, Jun
Abstract: As a type of mechanical stimulation, extracorporeal shockwave (ESW) has been widely used in the clinic to treat bone fracture delayed union and non-unions. A large number of studies have shown beneficial effects of ESW in promoting fracture healing by inducing bone regeneration; however, the underlying mechanisms remain unclear. ESW has been shown to induce the production of prostaglandin E2 (PGE2 ), which is essential for gap junction intercellular communication in response to mechanical stress. Among the 19 known gap junction subunits, connexin43 (Cx43) is the most prevalent for mediating the response of mechanical stress. However, to our knowledge, the effect of ESW on Cx43 expression has not been reported before. Herein, we propose that a crosstalk between PGE2 and Cx43 is involved in the enhancement of osteogenesis induced by ESW. We review the currently available data to propose an unrevealed, but important mechanism via which ESW treatment affects osteogenic differentiation of bone marrow stromal cells.